The S-BPM Architecture: A Framework for Multi-agent Systems - Rass, Stefan; Kotremba, Johannes; Singer, Robert (2013 IEEE/WIC/ACM International Joint Conferences on Web Intelligence (WI) and Intelligent Agent Technologies (IAT), 2013)
Commercially available business process management systems (BPMS) still suffer to support organizations to enact their business processes in an effective and efficient way. Recently, a method for modeling and execution of business processes, named subject-oriented business process management (S-BPM), gained attention. This methodology facilitates modeling of any business process using only five symbols and allows direct execution based on such models. Any process is defined as a network of independent and distributed agents which coordinate work through the exchange of messages. In this work, we present a framework and a prototype based on off-the-shelf technologies as a general execution platform for S-BPM process models and we can prove and demonstrate the principal architecture concept.